Hubungan Minat Membaca Di Kalangan Pelajar-Pelajar SMKA Di Seberang Perai Dengan Latar Belakang Keluarga Dan Persekitaran - Abd Wahab, Mat (1995)

(untitled)
This research emphasizes on reading interest among students in Seberang Perai government religious school. The research was done in Sekolah Menengah Kebangsaan Agama Al-Irshad, the only government religious school in the district of Seberang Perai. The research focuses on the factors influencing reading habits such as books, magazines and newspapers. With this research , the researcher tries to explain and give a clear picture of the actual situation. As one of the government religious secondary schools in the nation which obtains excellent results in the public examination, it is proper to study as how this school has achieved its standard. The research tries to see the association between parents income, gender, age, location and reading materials availability with reading interest. This research was carried out by using questionnaires survey method. The analysis was done by using SPSS for Windows Release 6.0. A total of 270 students were selected randomly from form one to form six as respondents. The tindings using the t-test and ANOVA showed that there was a significant difference between income of parents/guardians and interest in reading books. There was a significant difference between age and interest in reading magazines and newspapers. Gender and interest in reading magazines showed significant difference. Finally there was a significant difference between availability of obtaining newspapers and interest in reading newspapers. The result also showed that 87.0% of the respondents read newspapers and enjoy the main news. 98.9% read books and story books top the list whereas 93.0% read magazines. The ‘Dewan Siswa’ is the most favourite magazine. 76.3% of the respondents stated that their parents had influenced them to read. The importance of this research is that it gives a clear picture of students’ interest in reading. This is a good indicator for the school to enhance and foster the reading habit among its students and pave the way to an excellent reading culture